Ensuring the Possibility of Using a Standard Set of Filter Gas Masks in an Isolating Protection Mode - A. Yu. Kovalev; S. B. Blinov; S. A. Tkachenko; M. P. Shabelnikov; O. A. Kulazhin (Вестник войск РХБ защиты, 2024)
Combined type personal respiratory protection equipment, combining the functions of air purification and complete isolation from the environment, has not received significant development due to the complexity of the design, which limits their use. At the same time, as the accumulated experience of the actions of rescue military units of the civil defense forces, the Ministry of Emergency Situations of the Russian Federation and units of the radiation, chemical and biological protection troops of the Armed Forces of the Russian Federation shows, the use of combined type protective equipment in a number of cases is extremely necessary. The purpose of the work is to develop the design of a universal module connected to a filter gas mask to enable the implementation of a mode of complete isolation from the ambient air. Materials and methods. The justification for the design of the universal module was carried out on the basis of existing developments of design and circuit solutions for units and elements of the filter gas mask and self-contained breathing apparatus. Predictive assessment of the performance of the design of the removable module components was carried out by calculation in the Microsoft Excel 2013 environment using methods of aero- and hydrodynamic calculations of technological systems. The functionality of the main structural units of the module was tested in laboratory conditions while simulating the parameters of human external respiration. The discussion of the results. The following tasks were solved: the technical characteristics of the universal module were substantiated, ensuring the preservation of the indicators of the main protective, operational and ergonomic properties of filter gas masks and the design of the universal module with a predictive assessment of the performance of its main components; a physical model of the universal module was made; An experimental test of the performance of its main structural components was carried out. Conclusion. The results obtained confirmed the operability of the design and circuit solutions of the universal module, which ensures the implementation of a mode of complete isolation from ambient air in a standard set of filter gas masks.